Batteries: High Performance 3D Si/Ge Nanorods Array Anode Buffered by TiN/Ti Interlayer for Sodium‐Ion Batteries (Adv. Funct. Mater. 9/2015). (March 2015) - Yue, Chuang; Yu, Yingjian; Sun, Shibo; He, Xu; Chen, Binbin; Lin, Wei; Xu, Binbin; Zheng, Mingsen; Wu, Suntao; Li, Jing; Kang, Junyong; Lin, Liwei
Abstract : On page 1386, J. Li and co‐workers present 3D hexagonal Si/TiN/Ti/Ge NR arrays as anodes in sodium‐ion batteries (SIBs) with high reversible areal/specific capacity and superior cycling stability even imposed by high current densities. This kind of unique wafer‐scale 3D Si‐based composite electrode portends a promising future for lab‐on‐chip micro/nanoSIBs with practical applications in integrated circuit systems, micro/nanoelectro mechanical systems, or other smart electronic devices.